Avaliação da qualidade da água da chuva e da viabilidade de sua captação e uso - Hagemann, Sabrina Elicker (2009)
This paper aims to evaluate the rainwater quality in city of Santa Maria RS, identify the most suitable usages for it and to study the technical feasibility of its collection, through a reservoir dimension for exploitation. Two areas of study were chosen with different characteristics referring to their occupation. One of these areas is located next to RST 287 and the other is in Universidade Federal de Santa Maria campus. The rainwater was collected directly from atmosphere and from roofs, in order to analyze the changes in its quality after the passage for collection area. Each sample was divided in five compartments for collecting and storing separately the first five millimeters of rain. The characteristics of rainwater quality were evaluated through the following parameters: pH, electrical conductivity, turbidity, BOD5, COD, total solids, suspended solids, dissolved solids and Escherichia coli. In some events it was also analyzed: color, alkalinity, hardness, chlorides, iron, manganese, phosphate, ammonium, nitrate and sulfate. For storage reservoir dimension it was used a method proposed by Mierzwa et al (2007) and the results were compared to methods proposed by NBR 15527/07. It was observed that the rainwater quality has changed after its passage for collection area. In raw state, the rainwater could be used to non-potable purposes as recreation of primary contact, irrigation of vegetables, parks, gardens, sport and leisure fields, after the discard of two millimeters initial. If the rainwater was treated, it obtain quality compatible with other uses as toilet flushing. In relation to storing reservoir, it was evident that the most profits for an efficient attendance to a demand occur by a volum of 5.000 liters, for a daily demand of 529 liters.